Total-energy and entropy considerations as a probe of chemical order in amorphous silicon carbide - Denteneer, P. J H; Kelires, Pantelis C. (My University, 1998)
Total energy calculations of various atomic configurations, carried out within the pseudopotential-density-functional (PDF) formalism, show that partial chemical ordering is by far the most favored phase in amorphous silicon-carbon alloys. The random phase, on the other hand, is the least favored configuration. Configurational entropy contributions to the free energy are not able to reverse this picture, yielding an exceedingly high transition temperature.
Keywords: Silicon carbide; Entropy; Silicon; Energy